Activate to Eradicate: Inhibition of Clostridium difficile Spore Outgrowth by the Synergistic Effects of Osmotic Activation and Nisin - Nerandzic, Michelle M. (Public Library of Science, 2013)
BACKGROUND: Germination is the irreversible loss of spore-specific properties prior to outgrowth. Because germinating spores become more susceptible to killing by stressors, induction of germination has been proposed as a spore control strategy. However, this strategy is limited by superdormant spores that remain unaffected by germinants. Harsh chemicals and heat activation are effective for stimulating germination of superdormant spores but are impractical for use in a hospital setting, where Clostridium difficile spores present a challenge. Here, we tested whether osmotic activation solutes will provide a mild alternative for stimulation of superdormant C. difficile spores in the presence of germinants as previously demonstrated in several species of Bacillus. In addition, we tested the hypothesis that the limitations of superdormancy can be circumvented with a combined approach using nisin, a FDA-approved safe bacteriocin, to inhibit outgrowth of germinated spores and osmotic activation solutes to enhance outgrowth inhibition by stimulating superdormant spores. PRINCIPAL FINDINGS: Exposure to germination solution triggered ∼1 log(10) colony forming units (CFU) of spores to germinate, and heat activation increased the spores that germinated to >2.5 log(10)CFU. Germinating spores, in contrast to dormant spores, became susceptible to inhibition by nisin. The presence of osmotic activation solutes did not stimulate germination of superdormant C. difficile spores exposed to germination solution. But, in the absence of germination solution, osmotic activation solutes enhanced nisin inhibition of superdormant spores to >3.5 log(10)CFU. The synergistic effects of osmotic activation solutes and nisin were associated with loss of membrane integrity. CONCLUSIONS: These findings suggest that the synergistic effects of osmotic activation and nisin bypass the limitations of germination as a spore control strategy, and might be a novel method to safely and effectively reduce the burden of C.difficile spores on skin and environmental surfaces.